Impact of Intraoperative Ultrafiltration on the Development of Acute Kidney Injury in Chronic Kidney Disease Patients Undergoing Cardiac Surgery - Thana, Kanjana; Tepsuwan, Thitipong; Thana, Umpaipan (Biomedical Sciences and Clinical Medicine, 2022)
OBJECTIVE To evaluate the incidence and effectiveness of using ultrafiltration in chronic kidney disease (CKD) patients during cardiac surgery. METHODS A retrospective record review of all chronic kidney disease patients who underwent cardiac surgery at a university hospital medical center in Thailand from January 2013 to December 2018. RESULTS Data from 306 eligible CKD patients were analyzed. The average age of patients was 63.89 ± 10.05 years. Two-hundred and twenty-two patients were male (72.2%). More than half of the patients (162/306 or 52.9%) underwent ultrafiltration (UF) during cardiopulmonary bypass (CPB). During the postoperative period, CKD patients who had received the UF were more likelyto have higher postoperative serum creatinine after surgery and on post-operation day 1 (p < 0.01). However, there was no statistically significant difference in the occurrence of acute kidney injury (AKI) among CKD patients who received ultrafiltration and those who did not. CONCLUSIONS In this study, the ultrafiltration intervention did not reduce the incidence of AKI among patients with CKD who underwent cardiac surgery during CPB. However, further prospective investigation is needed to fully evaluate the contribution of ultrafiltration in reducing the risk of developing postoperative AKI among patients with preexisting renal failure.